Kelemahan Implementasi Penganggaran Berbasis Kinerja di Indonesia: Scoping Review - Fauziah, Rischa Inung; Rachmawati, Desiana; Wicaksana, Fandi Galang; Widayati, Wiwik; Hidayat, Taufiq (ITB AAS Indonesia Surakarta, 2025)
This study aims to identify the main obstacles in the implementation of performance-based budgeting (PBB) in the Indonesian public sector using a scoping review approach through the PRISMA framework. A literature review covering the period 2020–2024 reveals that although PBB has been promoted as a public financial reform instrument to enhance accountability, efficiency, and effectiveness in budget management, its implementation still faces significant challenges. The key obstacles include: (a) performance indicators that are predominantly output-oriented rather than outcome-oriented, (b) inefficiencies arising from the mismatch between planning and realization, (c) limited availability of performance data and non-integrated information systems, (d) insufficient human resource capacity in designing and evaluating performance-based budgets, and (e) bureaucratic organizational culture that remains spending-oriented and subject to political intervention. The findings also highlight several enabling factors for successful PBB implementation, namely competent human resources, organizational commitment, a functioning reward and punishment system, and managerial support in providing adequate infrastructure. Therefore, the refinement of PBB can be achieved through continuous human resource training, the application of performance-based reward and punishment, the strengthening of information technology infrastructure, organizational cultural transformation towards a result-oriented approach, and transparent, data-driven evaluation. These findings are expected to provide both theoretical and practical contributions to improving PBB practices in Indonesia and to enrich the literature on public financial management. Keywords: Performance-Based Budgeting, Implementation Barriers, Accountability, Budget Efficiency, Human Resources, Organizational Culture